2022
DOI: 10.1021/acscatal.2c04959
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Synthesis of Anilines via Ni-Catalyzed Coupling of Aryl Halides with Ammonium Salts

Abstract: Easy, efficient, and economic synthesis of anilines remains an important challenge in synthetic chemistry. In this study, a Ni(OAc) 2 -bipyridine complex is shown to readily catalyze the amination of aryl halides with ammonium salts under direct excitation of light, allowing a broad array of aryl chlorides and bromides to be converted into the corresponding primary (hetero)arylamines in the absence of an external photosensitizer. Late-stage modification of drug molecules and 15 N-labeling of primary aryl amine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 116 publications
0
21
0
Order By: Relevance
“…Complementing the dual catalytic strategy, single Ni(II) catalyst mediated photochemical C−N coupling has been achieved, [10–13] taking the advantage of nickel photochemistry while avoiding the need to use exogenous photocatalyst. In our earlier studies, aryl chlorides were found to exhibit high reactivity and good functional group compatibility in some photochemical C−N coupling reactions under the direct irradiation of a Ni(II)‐bipyridine complex [13a,c–d] . Mechanistic studies suggest that the efficient generation of active Ni(I) species and subsequent oxidative addition with aryl chlorides may be a key factor in achieving these photochemical C−N coupling reactions through the Ni(I)/Ni(III) cycle [14–16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementing the dual catalytic strategy, single Ni(II) catalyst mediated photochemical C−N coupling has been achieved, [10–13] taking the advantage of nickel photochemistry while avoiding the need to use exogenous photocatalyst. In our earlier studies, aryl chlorides were found to exhibit high reactivity and good functional group compatibility in some photochemical C−N coupling reactions under the direct irradiation of a Ni(II)‐bipyridine complex [13a,c–d] . Mechanistic studies suggest that the efficient generation of active Ni(I) species and subsequent oxidative addition with aryl chlorides may be a key factor in achieving these photochemical C−N coupling reactions through the Ni(I)/Ni(III) cycle [14–16] .…”
Section: Introductionmentioning
confidence: 99%
“…The solvents have important influence on the yields, with the mixture of PhMe and THF being the best (Table S5). Moreover, no desired product was obtained at room temperature (entry 12), possibly because heating is required to promote the oxidative addition of Ni(I) with the aryl halide [13d] . Finally, control experiments revealed that the reaction did not proceed in the absence of nickel catalyst (entry 13).…”
Section: Introductionmentioning
confidence: 99%
“…However, it still required the use of elevated temperature and long‐wave Uv‐light. Very recently, it is good to mention that the same group extended the strategy to ammonium salts as the nucleophiles coupled with aryl chlorides as well [23] (Scheme 5).…”
Section: The Niii Complexes As the Reservoir Of Active Nii Complexes ...mentioning
confidence: 99%
“…Recently, to diminish the use of exogenous noble metal-based photocatalysts, diverse visible-light-induced nickel-catalyzed carbon–heteroatom couplings have been developed via homolysis of Ni II –Y (Y = C, N, O, etc.) bonds to form the active Ni I complex but not for Ni II –S bond. , The rupture of the Ni–S bond to generate the Ni I complex from nickel­(II) thiolates is challenging under thermal conditions because thiolate anions are strong ligands to metals . In contrast, the visible-light excitation might promote homolysis of the Ni II –S bond via the ligand to metal charge transfer (LMCT) process to afford nicke­(I) species and give C–S coupling products in the Ni I /Ni III self-sustained catalytic cycle (Figure b).…”
mentioning
confidence: 99%